On becoming a servant-leader the private writings of Robert K. Greenleaf - Greenleaf, Robert K. (San Francisco Jossey-Bass Publishers, 1996)
Delve into the personal writings of the grandfather of the modern empowerment movement in business leadership. In this collection of previously unpublished works, eminent writer, consultant, and lecturer Robert Greenleaf shares his personal and professional philosophy, which postulates that true leaders are those who lead by serving others. Spanning a time frame of fifty years, these essays and lectures touch on such key issues as power, ethics, management, organizations, and servanthood. And they offer the reader a wealth of practical suggestions and useful information garnered through the course of a remarkable career.
Includes bibliographical references (p. 379-380) and index.
Keywords: Leadership